Feasibility and performance analysis of ordinary concrete prepared with autoclaved spherical porous aggregates from waste rock sawdust - Qingfeng Guan; Yongxiang Zhou; Faguang Leng (Case Studies in Construction Materials, 2024)
The escalating accumulation of waste rock sawdust in the stone processing industry poses significant environmental challenges. This study investigates the recycling of this waste into spherical porous aggregates (SPA) using autoclaving for integration into ordinary concrete. Properties like moisture transportability and chloride ion permeability resistance were evaluated. Findings indicate an enhanced flowability in SPA-incorporated concrete, with a 28-day strength of 56 MPa and a density exceeding 2300 kg/m³ . However, elevated SPA content correlated with increased drying shrinkage, water penetration, and electrical flux. Microscopic analysis revealed a compromised pore structure due to higher coarse pore content in SPA. Effective improvement in concrete durability is achievable by limiting SPA content to 20 vol%, reducing the water-binder ratio, or employing stronger SPA. The study validates the potential for scalable waste rock sawdust disposal through its use in ordinary concrete.